2013
DOI: 10.4236/ojrd.2013.31003
|View full text |Cite
|
Sign up to set email alerts
|

Bronchospasm Diagnosis in Motorcycle Taxi Drivers Exposed to Automotive Pollutants in Porto-Novo

Abstract: Background: In African cities, chronic exposure to pollutants is the most common public health problem faced daily by motorcycle taxi drivers. In Benin, studies conducted on motorcycle drivers, have shown the presence of nitrogen oxides, carbon monoxide, sulfur dioxide, volatile organic compounds and particulate matter in ambient air, which may affect lung function. Aims: This study aims to diagnose potential respiratory problems among 48 motorcycle taxi drivers (47.02 ± 8.75 years) compared to a control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The sample consisted predominantly of young black, married adults with low schooling. These findings confirm the results of national and international studies 4,9,14,15 and it should be noted that the predominance of this ethnicity/skin color may be associated with the performance of the research in a region strongly marked by African descent origin 16 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The sample consisted predominantly of young black, married adults with low schooling. These findings confirm the results of national and international studies 4,9,14,15 and it should be noted that the predominance of this ethnicity/skin color may be associated with the performance of the research in a region strongly marked by African descent origin 16 .…”
Section: Discussionsupporting
confidence: 87%
“…Motorcycle taxi drivers are often submitted to poor working conditions 14 , whose work involves intense rhythms and overwork, urban violence, stress, tiredness, physical wear and emotional distress, sleep disorders, fatigue, irritability, sedentary lifestyle, exposure to pollution, among others problems. The lowest exposure to these factors may contribute to the promotion and maintenance of work capacity, relating to a better perceived quality of life in the physical realm.…”
Section: Discussionmentioning
confidence: 99%
“…Diesel gas emissions in the gaseous phase comprise several toxic gases, including nitrogen dioxide (NO 2 ) and carbon monoxide (CO) [3]. In Benin, the inhalation of car pollutants due to the relatively long duration induces respiratory disorders [4] in motorcycle taxi drivers exposed to a CO concentration greater than nine (09) ppm [5]. Cachon et al [6] showed that the exposure of human bronchial epithelial cells to particulate matter (PM 2.5 and PM > 2.5) collected in the city of Cotonou (Benin) induces the significant secretion of pro-inflammatory cytokine proteins (TNF-α) and an increase in the level of MDA, regardless of the duration of the exposure (24, 48 and 72 h).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study conducted among 400 motorcycle taxi drivers, after analysis of the ambient air collected at intersections and motorcycle taxi parks, showed peak concentrations of CO of 38.6 ppm (parts per million) in the morning and 78.6 ppm in the afternoon [ 8 ] although national air quality in Benin for CO is 32 ppm (1 hour- average exposure) [ 11 ]. A different study carried out in Benin using self-report questionnaires distributed to motorcycle taxi drivers, showed that 23% of the drivers had difficulty breathing [ 12 ]. But very little is known about the relationship between exceedances of air quality standards for carbon monoxide and respiratory health disorders among motorcycle taxi drivers.…”
Section: Introductionmentioning
confidence: 99%